2021
DOI: 10.1002/hast.1235
|View full text |Cite
|
Sign up to set email alerts
|

Does a Public Health Crisis Justify More Research with Incarcerated People?

Abstract: Covid‐19 has infected thousands and killed hundreds in prisons, jails, and immigration detention facilities across the United States. Responding to this crisis, leading medical researchers have called for expanding opportunities for people in prison to participate in vaccine trials. These calls, like current regulations, focus on individualized risk assessments around consent, coercion, and harm, while ignoring the unnaturalness of deprivation conditions in U.S. prisons. We need new frameworks of analysis that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Objections included the real and perceived pressure from authorities to participate, demands to participate to receive care that could otherwise not be afforded, risks associated with the vaccines being trialled, limited or no on-site clinical support for participants, and no guarantee that participants would benefit from the vaccines if they were found to be safe and effective. 59,61 These concerns tended to trump the perceived benefits of participation. Indeed, many publications raised the issue that recruiting trial participants from the prison population would reinforce the perpetual exploitation, abuse, and neglect of people in prison.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Objections included the real and perceived pressure from authorities to participate, demands to participate to receive care that could otherwise not be afforded, risks associated with the vaccines being trialled, limited or no on-site clinical support for participants, and no guarantee that participants would benefit from the vaccines if they were found to be safe and effective. 59,61 These concerns tended to trump the perceived benefits of participation. Indeed, many publications raised the issue that recruiting trial participants from the prison population would reinforce the perpetual exploitation, abuse, and neglect of people in prison.…”
Section: Discussionmentioning
confidence: 99%
“…45 Most included studies were published in countries of the Global North. More than half (n=25, 57%) were published in the United States; [36][37][38][39][40][41][42][43][44][45][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] five were published in the United Kingdom; [63][64][65][66][67] two were from Brazil; [68][69] and there was one publication each from Africa, 70 Canada, [71][72][73] and South Korea. 46 An additional nine papers focused on various world regions.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers raised the ethical arguments of need for informed consent, avoiding coercion, and minimising harm, recommending that oversight boards monitor trials and obtain input from these populations to enable their participation [47,48]. Publications raised further relevant issues for the prison population, including real and perceived pressure from authorities to participate in trials, pressure to participate to receive the care they cannot afford, uncertain risks of vaccines being trialled, limited or nonexistent on-site clinical support, and the absence of an agreement that people in prisons would benefit from the vaccines if they were found to be safe and effective [47,62].…”
Section: Themes From Included Studiesmentioning
confidence: 99%
“…Our analysis revealed that the majority of papers on vaccination trials were opposed to the inclusion of people in prisons. Objections included the real and perceived pressure from authorities to participate, demands to participate to receive care that could otherwise not be afforded, risks associated with the vaccines being trialled, limited or no on-site clinical support for participants, and no guarantee that participants would benefit from the vaccines if they were found to be safe and effective [47,62]. These concerns tended to trump the perceived benefits of participation.…”
Section: Plos Onementioning
confidence: 99%